Sweet evil eaudiobook - Higgins, Wendy (Sweet Trilogy, 2012)
Fans of Cassandra Clare's Mortal Instruments series will be drawn to Wendy Higgins's sexy, thrilling Sweet Evil series. What if there were teens whose lives literally depended on being bad influences? This is the reality for sons and daughters of fallen angels. Tenderhearted Southern girl Anna Whitt was born with the sixth sense to see and feel emotions of other people. She's aware of a struggle within herself, an inexplicable pull toward danger, but Anna, the ultimate good girl, has always had the advantage of her angel side to balance the darkness within. It isn't until she turns sixteen and meets the alluring Kaidan Rowe that she discovers her terrifying heritage and her willpower is put to the test. He's the boy your daddy warned you about. If only someone had warned Anna. Forced to face her destiny, will Anna embrace her halo or her horns?